(untitled) (International Current Pharmaceutical Journal, 2015)
A new simple, sensitive and specific procedure has been developed for determination of tenofovir disoproxil fumarate in bulk and pharmaceutical dosage forms using MBTH reagent. The purpose of this analytical validation procedure is to validate it by laboratory experiments to prove that the method meets the minimum standards for laboratory use. 3-methyl-2-bezothiazoline hydrazone reacts with the secondary amine group of tenofovir in the presence of oxidizing agent, ferric chloride. The resulting apple green coloured chromogen when measured spectrophotometrically in visible region (i.e., 400-800nm) shows a maximum absorbance at 626.5nm. This method can be successfully applied for the determination of drug content in pharmaceutical formulations. The results of analysis have been validated statistically. DOI: http://dx.doi.org/10.3329/icpj.v4i4.22620 International Current Pharmaceutical Journal, March 2015, 4(4): 378-381